This preview shows pages 1–4. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Thus by (3) the general solution of the ode is x ( t ) = e 2 t ( A cos t + B sin t ) . The derivative is ˙ x ( t ) = 2 e 2 t ( A cos t + B sin t ) + e 2 t ( A sin t + B cos t ) . Applying the initial conditions x (0) = 1 = A, ˙ x (0) = 0 = 2 A + B, which give us A = 1 , B = 2 . Therefore, x ( t ) = e 2 t (cos t + 2sin t ) . Clearly when t increases, e 2 t decays to zero and cos t + 2sin t oscillates. Thus x ( t ) has decaying oscillation for large t. 2 Remark . In general note that μ 6 = 0, it is easy to see that for the solu tion (3) when t increases there are three cases: (i) If λ > 0 then x ( t ) has growing oscillation; (ii) If λ = 0 then x ( t ) has steady oscillation; (iii) If λ < 0 then x ( t ) has decaying oscillation. 2 Case 3. When Δ = 0 , (2) has only one real root given by r = b 2 a . Then the solution of (1) can be written as x ( t ) = ( c 1 + c 2 t )exp b 2 a t ¶ , (4) with c 1 , c 2 constants. Example 2. Consider the initial value problem ¨ x + ˙ x + 0 . 25 x = 0 , x (0) = 2 , ˙ x (0) = b. Find the solution as a function of b and then determine the critical value of b that separates solutions that grow positively from those that eventually grow negatively . 2 The characteristic equation is r 2 + r + 0 . 25 = ( r + 1 / 2) 2 = 0 , with a repeated root r = 1 / 2 . Therefore the general solution is x ( t ) = ( c 1 + c 2 t ) e t/ 2 with derivative ˙ x ( t ) = ‡ c 1 2 + c 2 c 2 2 t · e t/ 2 ....
View
Full
Document
This note was uploaded on 01/28/2011 for the course MATH 150 taught by Professor T.qian during the Spring '09 term at HKUST.
 Spring '09
 T.Qian
 Derivative

Click to edit the document details